Factors Affecting Compliance With Colorectal Cancer Screening Among Households Residing in the Largely Haitian Community of Little Haiti, Miami-Dade County, Florida. Issue 18 (May 2015) - Wilcox, Meredith Leigh; Acuña, Juan Manuel; de la Vega, Pura Rodriguez; Castro, Grettel; Madhivanan, Purnima; Nzeako., Ugo
<x xml:space="preserve">Abstract</x> Abstract The United States Black population is disproportionately affected by colorectal cancer (CRC) in terms of incidence and mortality. Studies suggest that screening rates are lower among Blacks compared with non-Hispanic Whites (NHWs). However, studies on CRC screening within Black subgroups are lacking. This study examined disparities in blood stool test (BST) compliance and colonoscopy use by race/ethnicity (Haitian, NHW, non-Hispanic Black [NHB], and Hispanic) among randomly selected households in Little Haiti, Miami-Dade County, Florida. This study used cross-sectional, health and wellness data from a random-sample, population-based survey conducted within 951 households in Little Haiti between November 2011 and December 2012. BST compliance and colonoscopy use were self-reported and defined, conservatively, as the use of BST within the past 2 years and the ever use of colonoscopy by any household member. Factors associated with BST compliance and colonoscopy use were identified using logistic regression models. Analyses were restricted to households containing at least 1 member ≥50 years (n = 666). Nearly half of the households were compliant with BST (rate [95% confidence interval (CI)] = 45% [41%–49%]) and completed colonoscopy (rate [95% CI] = 53% [49%–58%]). Compliance with BST was not associated with race/ethnicity (P = 0.76). Factors independently associated with BST compliance included low educational attainment (adjusted odds ratio [AOR] = 0.63, P = 0.03), being single (AOR = 0.47, P = 0.004), retirement (AOR = 1.96, P = 0.01), and the presence of diagnosed health problems (AOR = 1.24, P = 0.01). Colonoscopy use was lower among Haitian households (46%) compared with NHW (63%), NHB (62%), and Hispanic households (54%) (P = 0.002). Factors independently associated with colonoscopy use included identifying as NHB (compared with Haitian) (AOR = 1.80, P = 0.05), being single (AOR = 0.44, P = 0.001), retirement (AOR = 1.86, P = 0.02), lack of continuous insurance (AOR = 0.45, P < 0.001), and the presence of diagnosed health problems (AOR = 1.44, P < 0.001) and physical limitations/disabilities (AOR = 1.88, P = 0.05). Compliance with BST and use of colonoscopy are low within households in the Little Haiti community. Significant disparities in the use of colonoscopy exist between Haitian and NHB households. Barriers and facilitators of colonoscopy within each racial/ethnic group need to be identified as the next step to developing culturally appropriate, community-based interventions aimed at increasing colonoscopy use in this large minority population.